The Influence Of Glass Ceiling Perceptions And Organizational Culture On Women's Career Development: The Mediating Role Of Self-Efficacy - Ririn Budiarti; Etty Puji Lestari; Mafizatun Nurhayati (Jurnal Indonesia Sosial Teknologi, 2023)
This study aims to analyze the mediating role of self-efficacy in the influence of glass ceiling perception and organizational culture on women's career development. The study population was female state civil servants occupying Echelon II, Echelon III, and Echelon IV positions in the Rejang Lebong Regency Government totaling 141 respondents. This study used a survey method with a research instrument in the form of a questionnaire/questionnaire. To certify the validity and reliability of the instrument will be tested through SPSS and data analysis will be carried out with the Partial Least Square-Structural Equation Model (SEM PLS). The results showed that the perception of the glass ceiling did not affect women's career development. Organizational culture positively influences women's career development. Self-efficacy has a positive effect on women's career development. The study found that self-efficacy cannot mediate glass ceiling perceptions of women's career development. However, self-efficacy mediates organizational culture towards women's career development